Meta-Analysis: The Association of Airborne Fungi With Children’s Health Level. - ZAKARIA HAMID; Adibah Najwa Omar; Pang Jyh Chyang (Proceeding of International Conference on Science, Health, And Technology, 2022)
Association of concentration of airborne fungi (CFU/m3) among school-age children and their health level was very worrying. They were tempted to stay indoors such as, bedroom, playroom, and classroom. This study focused on how the concentration of airborne fungi (CFU/m3) affect the level of children’s health as we know that children tend to be exposed and easy to get pulmonary infection and dysfunction. Even though the children are the most vulnerable to illness, there is less concern about indoor air quality. Owing to the early development of their immune system, lungs, and other organs, children are extremely vulnerable to disease. In general, a nursery is a designated area where infants are cared for. A nursery, on the other hand is described as any facility designed for the purpose of providing care or maintenance for children under the age of six. The 0-1 year old group and the 2-4 year old group are the two primary groups of young children. While school where by there’s classroom which is classroom is a place where education is provided. When considering the time that children spend there and the activities that they participate in. Meanwhile the residence means a place where someone lives, or the condition of living somewhere. There are two of parameters associated to the concentration of airborne fungi (CFU/m3) and indirectly cause pulmonary problem to the children. They are temperature and humidity. There is also the differentiation of the concentration of airborne fungi (CFU/m3) indoor and outdoor. As conclusion, the concentration of airborne fungi (CFU/m3) are significant to the temperature and relative humidity and the concentration of airborne fungi (CFU/m3) indoor is significant due to poor ventilation and maintenance.